The Representation of Psychological War-Related Traumas in the Literary Works of Contemporary Burundian and Ukrainian Writers: African and European Perspectives - Audace Mbonyingingo; Olena Moiseyenko; Dmytro Mazin (Kyiv-Mohyla Humanities Journal)
The article explores the representation of psychological traumas afflicted by war in contemporary literary writing by Burundian (African) and Ukrainian (European) authors who were witnesses of the events described in their works. Based on the existing linguistic and psychological theoretical approaches to the phenomenon of a mental wound, a comparative perspective is provided on the nature, literary, and linguistic manifestations of psychological trauma in Burundian novels by Antoine Kaburahe and Marie-Therese Toyi, presenting the tragic, but stoic experience during the civil war in the East African country, and the shocked, but resilient experience of Ukrainian civilians during the full-scale aggression of the russian federation in the Ukrainian diary (Serhiy Zhadan) and essay writing (Ilya Kaminsky, Ludmila Khersonsky, Zarina Zabrisky, Elena Andreychykova, Andrei Krasniashikh) available in English translation. The implemented analysis allows for a deeper understanding of the effects of wartime psychological trauma on the lives of an individual. Due to a more distant time perspective, the protagonists of Burundian texts reveal both the tragedy of the interethnic civil war conflict and the importance of addressing the causes of the conflict to prevent its replication in the future. In the Ukrainian texts, the initial stage of psychological trauma obtaining can be observed, which accounts for a range of the related emotional states among the characters who do not fully realize yet the traumatization process they have been going through during the first days and weeks of the russian military invasion. The narrative structure of the Burundian and Ukrainian texts was also highlighted, which helped identify traces of oral story-telling tradition (African texts) and broad allusions to the historical and cultural phenomena (Ukrainian texts).